Education of Motion Qualities of Speed in Football Players - S.K. Tashpulatov (Web of Journals Publishing, 2023)
This article provides brief information on training quickness and movement qualities in football players.
Keywords: Quick strength, football, movement speed, sport, activity, success, training, positive preparation, speed.